Kontrak tukaran matawang asing melalui internet: Satu tinjauan hukum - Azhar, Alias; Zainol, Mohd Zaki; Abdul Rahman, Mohd Nizho (UUM College of Law, Government and International Studies, 2015)
Foreign currency exchange contracts or foreign exchange (forex) began to arise when there is an international trade transaction involves two countries using different currencies. The legal assessment of the said issue should apply methods of interpretation and understanding of the terms to be applied in the contract.Terms such as leverage, hedging (hedging) and swap are thoroughly evaluated based on a practical modus operandi allowing for the precise legal assessment.This article discusses the contractual issues and modus operandi of foreign currency transactions and its application from the practical aspects using the Internet.Discussion on the legal assessment is based on the Islamic law of transactions on applied type of contract ('akad), the use of hedging and leverage in foreign exchange contracts via the Internet.